Effects of Conditioning Contractions on Lower-Body Explosive Force Post-Static Stretching - Li, Ming; Kim, Youngsuk; Guo, Weishuai; Fan, Penglei; Wang, Junsig; Kim, Sukwon (International Journal of Sports Medicine, 2024)
The present study assessed the impacts of two distinct protocols, static stretching (StS, 4 sets of 30 seconds) and static stretching combined with conditioning contractions (10 repetitive drop jumps) (SC), on neuromuscular response and rate of force development (RFD) in the lower limbs during squat jumps (SJs) at varying initial knee-joint angles (60°,90°,120°). Twelve participants completed three randomized experimental trials (no intervention, StS intervention, and SC intervention). Except for the intervention segments, each trial included standardized warm-ups and SJs at three different angles. Data were collected using a 3-dimensional injury motion capture system, an electromyography (EMG) recording system, and a force platform. The collected EMG data were subjected to amplitude calculations, while force-time data were used for RFD computation. Neither StS nor SC significantly impacted the average or peak EMG amplitudes of the five muscles examined (p>0.05). However, at an initial knee-joint angle of 120°, the StS group demonstrated significantly lower RFD values at three distinct phases (0–50 ms, 50–100 ms, and 0–peakforce) compared to those seen in the SC and control groups (p<0.05). For activities starting with a knee-joint angle of 120°, it is recommended to either avoid StS or combine it with ten repetitive drop jumps to mitigate any potential negative impact on explosiveness.
Keywords: electromyography; muscle activation; rate of force development; force-time characteristics